Non-stomatal processes reduce gross primary productivity in temperate forest ecosystems during severe edaphic drought. (26th October 2020) - Gourlez de la Motte, Louis; Beauclaire, Quentin; Heinesch, Bernard; Cuntz, Mathias; Foltýnová, Lenka; Šigut, Ladislav; Kowalska, Natalia; Manca, Giovanni; Ballarin, Ignacio Goded; Vincke, Caroline; Roland, Marilyn; Ibrom, Andreas; et al.
Abstract : Severe drought events are known to cause important reductions of gross primary productivity ( GPP ) in forest ecosystems. However, it is still unclear whether this reduction originates from stomatal closure (Stomatal Origin Limitation) and/or non-stomatal limitations (Non-SOL). In this study, we investigated the impact of edaphic drought in 2018 on GPP and its origin (SOL, NSOL) using a dataset of 10 European forest ecosystem flux towers. In all stations where GPP reductions were observed during the drought, these were largely explained by declines in the maximum apparent canopy scale carboxylation rate V CMAX, APP (NSOL) when the soil relative extractable water content dropped below around 0.4. Concurrently, we found that the stomatal slope parameter ( G1, related to SOL) of the Medlyn et al . unified optimization model linking vegetation conductance and GPP remained relatively constant. These results strengthen the increasing evidence that NSOL should be included in stomatal conductance/photosynthesis models to faithfully simulate both GPP and water fluxes in forest ecosystems during severe drought. This article is part of the theme issue 'Impacts of the 2018 severe drought and heatwave in Europe: from site to continental scale'.